[Works of Theodore Parker] - Parker, Theodore (American Unitarian Association, 1907)
v.1. A discourse of matters pertaining to religion. -- v.2. Theism and atheism. -- v.3. Sermons of religion. -- v.4. The transient and permanent in Christianity. -- v.5. Lessons from the world of matter and of man. -- v.6. The world of matter and the spirit of man. -- v.7. Historic Americans. -- v.8. The American scholar. -- v.9. Sins and safeguards of society. -- v.10. Social classes in a republic. -- v.11. The slave power. -- v.12. The rights of man in America. -- v.13. Autobiography, poems and prayers. -- v.14. Saint Bernard and other papers. -- v.15. Index.